958 Fatal Human Bocavirus Infection in a Boy with Ipex-Like Syndrome and Vaccine-Acquired Rotavirus Enteritis Awaiting Stem Cell Transplantation. (October 2012) - Klinkenberg, D; Kobbe, R; Schneppenheim, R; Müller, I; Blohm, M; Malecki, M; Schildgen, V; Schildgen, O
Abstract : We report about a 21-month-old boy presenting with chronic diarrhea and obstructive lung disease since infancy. His older brother, the first male child of non-consanguine Egyptean parents, had died at the age of 20 months suffering from BCGitis and severe CMV infection, suggesting a severe primary immundeficiency syndrome. We found immunological dysregulation, endocrine dysfunction and enteropathy compatible with IPEX syndrome, therefore the child was listed for stem cell transplantation (SCT). FOXP3 gene showed no IPEX associated mutations, but sequencing IL2RG we found an mutation in Exon 2 associated with x-linked IPEX-like SCID (c.252C>A, p.N84K). The pulmonary condition of the boy deteriorated and he was admitted on the ICU, where he was mechanically ventilated ever since. After common respiratory infections were excluded, chronic human bocavirus (hBoV) was identified by multiplex-PCR as the primary causative pulmonary agent causing his respiratory failure. HBoV was found in decreasing quantity in respiratory material, blood and stool specimen. Interestingly, chonic rotavirus shedding was notified in repetitive stool specimen. As the boy had been vaccinated against rotavirus, vaccine-aquired chronic infection was suspected and confirmed by typing of a vaccine virus specific gene variant. The boy died before SCT could be preformed. Since its dicovery, there is an ongoing discussion if hBoV can cause serious infections or represents only a harmless ″bystander″. This case report shows that hBoV can result in lethal respiratory infections in immunocompromised children.